A Conceptual Framework for Evaluation of Accreditation Surveyors of Iran Hospitals - Abbas Salarvand; Ebrahim Jaafaripooyan (Kerman University of Medical Sciences, 2019)
A Conceptual Framework for Evaluation of Accreditation Surveyors of Iran Hospitals   Salarvand Abbas1, Jaafaripooyan Ebrahim2*   1. MSc in Healthcare Management, Apapdana Hospital, Tehran, Iran 2. Associate Professor, Department of Health Management and Economics, School of Public Health, Tehran University of Medical Sciences, Tehran, Iran *Correspondence: School of Public Health, Tehran University of Medical Sciences, Enqelab Square, Tehran, Iran Tel: 00982142933058                                               Email: jaafaripooyan@tums.ac.ir Abstract: Background & Objectives: Accreditation, as a known method for evaluation of health care centers, is used with the aim of enhancing healthcare quality in the health systems of different countries and its success has a direct relation to the effective performance of its surveyors. So, the purpose of this study was to provide a conceptual framework for evaluating the accreditation surveyors of Iran hospitals. Methods: This qualitative study with a phenomenological approach was conducted in 2018 through eliciting the views of 30 expert and experienced interviewees in the field of hospital accreditation at the Ministry of Health, medical universities, hospitals, as well as accreditation surveyors selected purposefully with maximum diversity. Data were collected through semi-structured interviews and analyzed using content analysis. Results: A total of 4 main codes and 28 sub-codes were identified. Main codes included necessity and importance, principles and requirements, structure and methods of surveyors' evaluation. Conclusion: The results of this study can provide an effective framework for health system administrators in evaluation of accreditation surveyors of Iranian hospitals. In other words, continuous evaluation of accreditation surveyors' performance using different methods based on the principles and requirements found in this study can lead to the performance improvement of accreditation surveyors and finally the achievement of the accreditation goals. Keywords: Hospital accreditation, Accreditation surveyors' management, Accreditation surveyors' evaluation   Citation: Salarvand A, Jaafaripooyan E. A Conceptual Framework for Evaluation of Accreditation Surveyors of Iran Hospitals. Journal of Health Based Research 2019; 4(4): 421-36. [In Persian]